El proceso de toma de decisiones como competencia en la formación del ingeniero mecánico - Lianny Sánchez López (2023)
Nowadays, the importance of training an engineer according to the needs of the environment in which he/she lives and develops has been emphasized. The purpose of this work was to analyze the relationships established between teaching and learning approaches in the training of mechanical engineers, as a way to develop the decision-making competence through the use of the case study. A mixed research approach was assumed with a descriptive scope and a sequential explanatory design. A non-probabilistic purposive sampling was used. The sample consisted of students and professors of Mechanical Engineering at the Federal University of Minas Gerais. Several instruments were used, such as surveys, interviews and the case study method. It was found that the professors, although declaring to use an approach focused on conceptual change, their practices are still based on traditional teaching methods where the transmission of knowledge is privileged and contradictions were appreciated regarding the use of the case study, since the professors do not always have the knowledge for its adequate use. The students showed indicators related to the use of a deep learning approach, although sometimes they use superficial strategies. It was found that it is in the discussion space where the formation of the decision-making competence is fostered, based on the participants' analyses and the questions asked by the teacher during the class condition. It was found that it is necessary to conduct the decision-making process in its different stages so that the student takes a position and defines the decision to be assumed.